2019
DOI: 10.1128/jvi.00103-19
|View full text |Cite
|
Sign up to set email alerts
|

The Latency-Associated Transcript Inhibits Apoptosis via Downregulation of Components of the Type I Interferon Pathway during Latent Herpes Simplex Virus 1 Ocular Infection

Abstract: The herpes simplex virus (HSV-1) latency-associated transcript (LAT) has been shown to inhibit apoptosis via inhibiting activation of proapoptotic caspases. However, the mechanism of LAT control of apoptosis is unclear, because LAT is not known to encode a functional protein, and the LAT transcript is found largely in the nucleus. We hypothesized that LAT inhibits apoptosis by regulating expression of genes that control apoptosis. Consequently, we sought to establish the molecular mechanism of antiapoptosis fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 83 publications
2
32
0
Order By: Relevance
“…However, on days 2 and 4 p.i., WT mice infected with LAT(Ϫ) virus had higher virus titers than the other three groups ( in the eyes of infected mice. Recently, we reported that LAT downregulates components of the type I IFN pathway in ocularly infected mice (27). As we reported previously (12,19), we did not detect any difference in virus titers between LT␣ Ϫ/Ϫ mice infected with LAT(ϩ) and LAT(Ϫ) virus ( Fig.…”
Section: Resultssupporting
confidence: 79%
“…However, on days 2 and 4 p.i., WT mice infected with LAT(Ϫ) virus had higher virus titers than the other three groups ( in the eyes of infected mice. Recently, we reported that LAT downregulates components of the type I IFN pathway in ocularly infected mice (27). As we reported previously (12,19), we did not detect any difference in virus titers between LT␣ Ϫ/Ϫ mice infected with LAT(ϩ) and LAT(Ϫ) virus ( Fig.…”
Section: Resultssupporting
confidence: 79%
“…However, the mechanism of LAT against apoptosis is still not fully understood. LAT down-regulates the activation of apoptotic caspases 3, 8 and 9 [19]. In vitro, the cleavage of caspase 8 and 9 was inhibited in wild type HSV infected nerve 2A cells, while LAT deletion mutant viruses did not [37], indicating that the function of LAT was achieved by inhibiting the activation of pro-apoptotic caspases.…”
Section: Introductionmentioning
confidence: 95%
“…LAT may promote HSV activation by inhibiting apoptosis [19]. To some extent, the survival of neuronal cells can be achieved [60] [61].…”
Section: Current Theory Of Lat Mediated Hsv Reactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…LAT is the only HSV-1 transcript abundantly expressed during latency (20,21). It is well established that LAT controls apoptosis (22)(23)(24)(25)(26)(27)(28)(29), which likely occurs via the type I interferon (IFN) pathway (30). In addition, LAT is responsible for CD8 ϩ T cell immune exhaustion, which is also essential for latency establishment (31,32).…”
mentioning
confidence: 99%